Successful Endovascular Treatment of Postbiopsy AVF in Transplanted Kidneys: Lessons Learned from Two Cases in Multiorgan Transplant Recipients - Želalić, Sven; Šimunov, Bojana; Maksimović, Bojana; Mužar, Rea; Laganović, Mario; Vidjak, Vinko (International Journal of Angiology, 2023)
Allograft biopsy is a cornerstone in the management of transplanted kidneys. It is a safe procedure, often performed in the outpatient setting. A rare complication is formation of a postbiopsy arteriovenous fistula (AVF). We present here a report of two cases of postbiopsy AVFs treated endovascularly. Selective embolization is a safe and effective method of treatment of postbiopsy AVFs in renal allografts.
Keywords: kidney; transplant; endovascular procedure; arteriovenous fistula; biopsy